The Effect of STEM Problem-Based Learning (PBL) on Student’s Scientific Literacy and Creative Thinking Skills in Ecology Material at SMPN 37 Medan - Sinambela, Aslinda; Sipahutar, Herbert (Journal of Biology Education, 2025)
The purpose of this study is to analyze the effect of applying the STEM problem-based learning on student’s scientific literacy and creative thinking skills in ecology material. This study was quasi experimental research with two group pretest posttest design. The population of this research were all of students of class VII SMP Negeri 37 Medan, academic 2024/2025. The sample of this research were taken by using class cluster random sampling technique consisted of eight classes. Class VII-D was experimental class taught by STEM problem-based learning model, Class VII-E was control class taught by conventional. The research instruments were multiple-choice tests to assess scientific literacy and essay tests to assess creative thinking skills. The data were analized by using t-test. The results showed that the STEM-based problem-based learning model had a greater effect on students' scientific literacy and creative thinking skills (p < 0.05) compared to the conventional learning model applied to the control class. Based on the results, it can be concluded that the STEM-based problem-based learning model significantly influenced students' scientific literacy and creative thinking skills at SMP 37 Medan.